Implementation of the Promethee Algorithm to Improve Data Accuracy in a Scholarship Selection Information System - Halimah, Diana Nur; Hasbi, Muhammad; Prabowo, Iwan Ady (Jurnal Ilmiah SINUS, 2024)
The scholarship selection process at X University has traditionally relied on manual methods, primarily focusing on the highest GPA, which often leads to financial constraints and potential biases. This research aims to address these issues by improving the selection process for scholarship admissions using the Promethee method. By introducing new criteria such as residence status, parental education, employment status, income, home ownership, number of dependents, and life score, the study seeks to provide a more comprehensive and fair assessment. Data collection methods include observation, interviews, and literature study to understand the concept of scholarship selection. The research applied the Promethee algorithm to 20 students who received scholarships from Panasonic in 2023. Confusion matrix analysis showed an accuracy level of 50%, with a precision value of 100% and a recall value of 50%. Despite the need for improved accuracy, it is hoped that the Promethee method can help the X University Student Agency determine fairer and more efficient scholarship selections. This research is expected to contribute positively to improving the scholarship selection process at X University with a focus on efficiency and fairness.